PERILAKU PENCARIAN INFORMASI KESEHATAN DI INTERNET PADA MASYARAKAT KOTA BANDUNG - Tania Putri Rizkiyah; Ira Dwi Mayangsari (Lembaga Penelitian Universitas Langlangbuana, 2020)
Human behavior in its relation with information is very complex, information seeking behavior is one of the part of it. Information seeking behavior is an activity that started from needs of a person to get informations. In this modern age, the internet is a media that makes information searching easier. Health is one of the type of information that recently has been searched by people on the internet. The purpose of this study are to discover what type of information is most searched, what source of information is often used, what source of information is having the highest level of credibility and trust, and the level of satisfaction of types, sources, credibility and trust in information resources in the health sector on internet according to the people of Bandung City. The method used in this study is quantitative descriptive. Respondents of this study are 100 people of Bandung city, using the Simple Random Sampling technique. Based on the results of the study, it was found that the type of health information that is most searched on the internet is disease and its treatment with a percentage of 84.75%. The most frequently used source of information to obtain health information on the internet is web sites run by organizations with a percentage of 77 , 25%. The highest source of information that has the highest level of credibility and trust in obtaining health information on the internet is web sites run by organizations with a percentage of 78.5%. Some types and sources of health information on the internet have not met the level of satisfaction while all sources of health information on the internet whose credibility and trustworthiness have been studied have met respondents' satisfaction.